Estudio de mejora de la productividad de la infraestructura civil, maquinaria y personal que labora en la Empresa Arrocera Molino Buenos Aires en Camaná - Castillo Justo, Gaston Adan Martin (2021)
Agricultural activity in the Camaná province of the Arequipa department is the main source of income for the approximately 70,000 citizens who live in this city. Rice and bean production are the 2 most important activities in economic activity. We have 7,500 arable hectares that are planted with rice in the “big season” that occurs between October and March of each year. In the "small campaign" 4,500 ha are planted. of Canarian beans (FC) and 3,000 ha. of other bread products take away. The production of these 7,500 ha reaches 90,000 tons of paddy rice. The process by which this paddy rice is converted into milled rice, ready for human consumption, is carried out by 20 mills that, at an average rate of 4,500 tons, satisfy the processing demand each year. This milled rice is sold by each producer in the same mill where it was processed, in containers of 50 kg each. The Buenos Aires Rice Mill (MBA) processes 5,000 tons of paddy rice annually from 200 farmers who produce an average of 25 tons each per season, produced in 2 ha at a rate of approximately 12.5 tons per hectare. The marked seasonality of rice production and the need to sell it quickly, mean that the MBA company processes its customers' rice in no more than 4 months a year. The rest of the year, all the facilities are practically unused. The present work describes how to use all this idle capacity of the company, in the processing of beans. The research carried out has the objective of achieving the efficient use of civil infrastructure, machinery and personnel that work throughout the year. With this, productivity is substantially improved and consequently the annual profits of the MBA company would increase.